Temporal sampling error analysis of the Earth's outgoing radiation from a Moon-based platform. Issue 18 (17th September 2019) - Ye, Hanlin; Guo, Huadong; Liu, Guang; Guo, Qing; Zhang, Lu; Huang, Jing
ABSTRACT: This study investigates the temporal sampling error on the Earth's outgoing radiation, with a potential Earth observation platform, the Moon-based platform. To simulate the Earth's outgoing radiation viewed from a Moon-based platform, we used the datasets of the NASA's Goddard Earth Observing System Version 5 (GEOS-5) systems as the truth. The analysis is proposed by sampling the simulated time series. The sampling uncertainty associated with a given sampling interval is measured by computing the Root-Mean-Square-Error (RMSE) of the original and subsampled time series. The effects of different sampling intervals are evaluated by maximum bias. The effects of different sampling time are estimated by comparing correlations between the subsampled time series of different start time at specific temporal interval and the origin. The results show that the temporal sampling errors have the characteristics of the periodical uncertainties and bias, and 4-h sampling interval is a turning point. The sampling interval larger than 4 h will result in large uncertainties and bias.